2000
DOI: 10.2307/3802997
|View full text |Cite
|
Sign up to set email alerts
|

Local and Landscape-Level Factors Influencing Black Tern Habitat Suitability

Abstract: Wetlands throughout eastern South Dakota were surveyed (1995-97) for foraging and nesting black terns (Chlidonias niger) to evaluate local and landscape factors influencing habitat suitability. We surveyed 834 randomly selected, semipermanent, and seasonal wetlands that were stratified by physiographic domain, wetland density, and wetland surface area. A discriminant function model was used in a geographic information system (GIS) to classify habitat suitability of all semipermanent wetlands in eastern South D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…Naugle (1997) reported small (6.5 ha) marshes, within a mixture of large and small wetlands, being used by Black Terns in high-density wetland landscapes in South Dakota. In a subsequent South Dakota study, the mean size of wetlands used was 18.9 ha (Naugle et al 2000). Researchers report that nesting typically occurs in water depths ranging from 0.5 m to 1.2 m (Currier 2000), but several studies have found it to be less (Dunn and Agro 1995).…”
Section: Rangewide Habitatmentioning
confidence: 99%
See 1 more Smart Citation
“…Naugle (1997) reported small (6.5 ha) marshes, within a mixture of large and small wetlands, being used by Black Terns in high-density wetland landscapes in South Dakota. In a subsequent South Dakota study, the mean size of wetlands used was 18.9 ha (Naugle et al 2000). Researchers report that nesting typically occurs in water depths ranging from 0.5 m to 1.2 m (Currier 2000), but several studies have found it to be less (Dunn and Agro 1995).…”
Section: Rangewide Habitatmentioning
confidence: 99%
“…or heath bogs (Peck and James 1983). Vegetation structure rather than species composition dictated suitability of nest substrates in eastern South Dakota (Naugle et al 2000).…”
Section: Rangewide Habitatmentioning
confidence: 99%
“…Several sources have identified the importance of landscape-level features on wetland use by waterbirds (Naugle et al 2000, Beatty et al 2014. In particular, waterfowl may use a variety of wetland types during spring migration, as a single wetland may not provide the necessary resources required by different species (Pearse et al 2011, Naugle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have found average local flight distances of about 3 to 5 km for Mallards (Link et al 2011, Beatty et al 2014 and Northern Pintails (Anas acuta; Pearse et al 2011), and several landscape characteristics have been shown to influence waterbirds at these spatial scales (Elphick 2008, Naugle et al 2000). …”
Section: Landscape-scale Habitat Variablesmentioning
confidence: 99%
See 1 more Smart Citation